EFISIENSI BIAYA PEMBANGUNAN GEDUNG PUSKESMAS BERBASIS REKAYASA NILAI DAN ANALISIS DAUR HIDUP - Vinantya Laksmi Ida Ayu Cri; I Putu Budi Artawan; Cokorda Agung Yujana (Politeknik Negeri Semarang, 2026)
The construction of health care facilities, such as Community Health Centers (Puskesmas), requires efficient cost planning given the limited local government budget. One approach to optimizing costs without reducing the building's function and quality is value engineering. This study aims to apply the value engineering method to the construction project for the UPTD Puskesmas III Building of the West Denpasar District Health Office to identify work items with potential for cost efficiency and to analyze the savings that can be achieved. The research method uses a case study approach with a value engineering work plan that includes the information stage, function analysis, creative stage, analysis stage, development stage, and recommendation stage. The analysis was carried out using breakdown cost analysis, cost-benefit ratio, life-cycle cost (LCC), and the Analytical Hierarchy Process (AHP). The results of the study indicate that work items such as floor slabs, doors and windows, ceramic floors and walls, and wall masonry and plastering have the greatest potential for value engineering. The implementation of the selected alternative resulted in a total cost savings of Rp1,308,373,475.75 or 7.67% of the total initial project cost. These results indicate that value engineering is effective in increasing construction cost efficiency without reducing the building's function or quality, making it suitable for application in health care facility construction projects.